Rapamycin Ameliorates Radiation-Induced Testis Damage in Mice - Yang, Juan; Xu, Rui; Luan, Yingying; Fan, Hancheng; Yang, Shuo; Liu, Jun; Zeng, Huihong; Shao, Lijian (Frontiers in Cell and Developmental Biology, 2022)
Male infertility is an important problem in human and animal reproduction. The testis is the core of male reproduction, which is very sensitive to radiation. The decline of male reproductive ability is a common trend in the world. Radiation is a physical factor leading to abnormal male reproductive function. To investigate the potential mechanisms of testicular damage induced by radiation and explore effective strategies to alleviate radiation-induced testis injury, C57BL/6 mice were irradiated with 8.0 Gy of X-ray irradiation. Testis and epididymis were collected at days 1, 3 and 7 after radiation exposure to analyze spermatogonia and sperm function. The results showed that radiation significantly destroyed testicular structure and reduced the numbers of spermatogonia. These were associated with mTORC1 signaling activation, decreased cellular proliferation and increased apoptotic cells in the irradiated testis. Rapamycin significantly blocked mTORC1 signaling pathway in the irradiated testis. Inhibition of mTORC1 signaling pathway by rapamycin treatment after radiation could significantly improve cell proliferation in testis and alleviate radiation-induced testicular injury after radiation exposure. Rapamycin treatment benefited cell survival in testis to maintain spermatogenesis cycle at 35 days after irradiation. These findings imply that rapamycin treatment can accelerate testis recovery under radiation condition through inhibiting mTORC1 signaling pathway.